2021
DOI: 10.3390/cancers13174247
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Post-Translational Modifications of Chemokines by CD26 in Cancer

Abstract: Chemokines are a large family of small chemotactic cytokines that fulfill a central function in cancer. Both tumor-promoting and -impeding roles have been ascribed to chemokines, which they exert in a direct or indirect manner. An important post-translational modification that regulates chemokine activity is the NH2-terminal truncation by peptidases. CD26 is a dipeptidyl peptidase (DPPIV), which typically clips a NH2-terminal dipeptide from the chemokine. With a certain degree of selectivity in terms of chemok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 305 publications
0
13
0
Order By: Relevance
“…Through their enzymatic activities, DPP4, FAP, APN, and ADAM17 mediate the proteolysis of bioactive peptides and cytokines, components of the extracellular matrix, and transmembrane proteins (receptors and adhesion molecules) [8,[10][11][12][13][15][16][17][18][19][20][21][22]. Ectoprotease interaction with their inhibitors or specific monoclonal antibodies (mAbs) has revealed that these ectoenzymes regulate intracellular key signalling pathways related to the modulation of major cell events (proliferation, survival, migration, angiogenesis) [11][12][13]18,20,[22][23][24][25][26][27][28][29] (Figure 1). The enzymatic activity of DPP4, FAP, APN, and ADAM17, even if it contributes, is not essential for signal transduction.…”
Section: Background and Introductionmentioning
confidence: 99%
“…Through their enzymatic activities, DPP4, FAP, APN, and ADAM17 mediate the proteolysis of bioactive peptides and cytokines, components of the extracellular matrix, and transmembrane proteins (receptors and adhesion molecules) [8,[10][11][12][13][15][16][17][18][19][20][21][22]. Ectoprotease interaction with their inhibitors or specific monoclonal antibodies (mAbs) has revealed that these ectoenzymes regulate intracellular key signalling pathways related to the modulation of major cell events (proliferation, survival, migration, angiogenesis) [11][12][13]18,20,[22][23][24][25][26][27][28][29] (Figure 1). The enzymatic activity of DPP4, FAP, APN, and ADAM17, even if it contributes, is not essential for signal transduction.…”
Section: Background and Introductionmentioning
confidence: 99%
“…However, our work can be related to the new studies using screening settings from individuals with adenomas and polyps or using panels of inflammatory biomarkers [ 11 , 14 , 15 ]. In fact, most data relate the changes of sCD26 levels with the immune system [ 18 , 24 , 25 , 26 , 40 , 41 ] with probable impact, as deduced from pre-clinical models, in DPP4 substrates such as certain chemokines [ 42 , 43 ]. This biomarker, therefore, is in line with a recently implemented Systemic Immune-Inflammation Index for CRC [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…CD26 is a type II transmembrane protein that recognizes chemokines with the penultimate proline or alanine and cleaves the NH2-terminal dipeptide [ 83 , 84 ]. Immunohistochemical analysis has shown that CD26 is highly expressed in MPM cells, indicating its pro-carcinogenic function and relevance as a prognostic marker [ 85 ].…”
Section: Exploring Other Targets To Detect More Specific and Effectiv...mentioning
confidence: 99%